2013
DOI: 10.1128/jvi.01070-13
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factor Binding Orientation and Dimerization May Influence Infectivity of Adenovirus-Coagulation Factor Complexes

Abstract: d Adenoviruses (Ads) are promising vectors for therapeutic interventions in humans. When injected into the bloodstream, Ad vectors can bind several vitamin K-dependent blood coagulation factors, which contributes to virus sequestration in the liver by facilitating transduction of hepatocytes. Although both coagulation factors FVII and FX bind the hexon protein of human Ad serotype 5 (HAdv5) with a very high affinity, only FX appears to play a role in mediating Ad-hepatocyte transduction in vivo. To understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 37 publications
(73 reference statements)
0
29
1
1
Order By: Relevance
“…If the same amount of virus was intravenously injected, a level of ectopic infection in distant organs should be comparable between AdSur-SYE and AdSur as previously reported [15]. It was recently reported that coagulation factor (F) X binds the hypervariable regions (HVR) of the hexon in an adenovirus, leading to liver infection [25,26]. The factor X enhances liver transduction by adenovirus vectors due to the protection of adenovirus from attack by the classical complementary pathway [27].…”
Section: Discussionmentioning
confidence: 69%
“…If the same amount of virus was intravenously injected, a level of ectopic infection in distant organs should be comparable between AdSur-SYE and AdSur as previously reported [15]. It was recently reported that coagulation factor (F) X binds the hypervariable regions (HVR) of the hexon in an adenovirus, leading to liver infection [25,26]. The factor X enhances liver transduction by adenovirus vectors due to the protection of adenovirus from attack by the classical complementary pathway [27].…”
Section: Discussionmentioning
confidence: 69%
“…It was recently reported that coagulation factor (F) X binds the hypervariable regions (HVRs) of the adenovirus hexon, leading to enhanced liver infection . Therefore, insertion of mutations in the FX‐binding domain of HVR and its replacement with HVR of other serotype adenoviruses markedly decreased the liver sequestration of the adenoviruses (Fig.…”
Section: Inhibition Of Liver Sequestrationmentioning
confidence: 97%
“…Upon discovery of CAR as the principal cell-surface attachment receptor for HAdv-C5 [39,40], attempts have been made to reduce HAdv-C5 hepatocyte infection via introduction of mutations into the knob domain of the fiber to ablate virus interaction with CAR. Using a set of HAdv-C5-based vectors ablated for fiber-mediated receptor interactions in mice, it was found that blood coagulation factors, namely FVII, FIX, and FX, can support efficient infection of virus-resistant cells and hepatocytes in vitro or upon isolated liver perfusion ex vivo [7,15,16]. Furthermore, HAdv-C5-based vectors ablated for interactions with both the CAR and cellular integrins retained their capacity to efficiently transduce hepatocytes after intravenous administration [55,56].…”
Section: Mechanisms Of Hadv Infection Of Hepatocytesmentioning
confidence: 99%
“…An extensive search for the mechanisms mediating the hepatic tropism of HAdv-C5 revealed that Gla domain-containing blood coagulation factors bind to the major virus capsid protein hexon and that coagulation factors can mediate virus entry into hepatocytes independent of the canonical virus cell attachment receptors, which interact with the fiber knob domain [7][8][9]15]. It was established that although several blood coagulation factors (F), including FVII [16], FIX [7], and FX [8,9], can bind to HAdv-C5 hexon, coagulation FX binds HAdv-C5 hexon with the highest, near picomolar, affinity [8,9]. Analysis of stoichiometry of FX binding to HAdv-C5 showed that a single virus particle can bind 240 FX molecules, indicating that the entire HAdv-C5 virus capsid, which is composed of 240 hexon trimer capsomers [17], is covered by FX after intravenous virus administration [8,18].…”
Section: Humoral Factors Affecting Hadv Bio-distribution After Intravmentioning
confidence: 99%